2022
DOI: 10.5551/jat.61630
|View full text |Cite
|
Sign up to set email alerts
|

Atorvastatin Reduces Circulating S100A12 Levels in Patients with Carotid Atherosclerotic Plaques - A Link with Plaque Inflammation

Abstract: Inflammation is involved in various processes of atherosclerosis development. Serum C-reactive protein (CRP) levels, a predictor for cardiovascular risk, are reportedly reduced by statins. However, several studies have demonstrated that CRP is a bystander during atherogenesis. While S100A12 has been focused on as an inflammatory molecule, it remains unclear whether statins affect circulating S100A12 levels. Here, we investigated whether atorvastatin treatment affected S100A12 and which biomarkers were correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 40 publications
(31 reference statements)
0
5
0
Order By: Relevance
“…In other words, PET/CT can detect even small changes in arterial wall inflammation, which is a unique property among other imaging techniques or biomarkers. So far, seven prospective studies have used scintigraphy to evaluate the impact of statins on carotid plaque inflammation by measuring target-to-background ratio (TBR) (n = 5 studies) [45][46][47][48] and/or standardized uptake value (SUV) (n = 3 studies) [39,49,50]. Most of them supported a significant reduction of arterial wall inflammation after either 3-month atorvastatin (10-80 mg/d) [46,[48][49][50] therapy, or 1-month atorvastatin (20 mg/d) [45] administration, or 6-month therapy with either simvastatin (10 mg/d), rosuvastatin (10 mg/d) [39], pitavastatin (2 mg/d), or pravastatin (10 mg/d) [39].…”
Section: Effects Of Statins On Fluorodeoxyglucose-positron Emission T...mentioning
confidence: 99%
See 3 more Smart Citations
“…In other words, PET/CT can detect even small changes in arterial wall inflammation, which is a unique property among other imaging techniques or biomarkers. So far, seven prospective studies have used scintigraphy to evaluate the impact of statins on carotid plaque inflammation by measuring target-to-background ratio (TBR) (n = 5 studies) [45][46][47][48] and/or standardized uptake value (SUV) (n = 3 studies) [39,49,50]. Most of them supported a significant reduction of arterial wall inflammation after either 3-month atorvastatin (10-80 mg/d) [46,[48][49][50] therapy, or 1-month atorvastatin (20 mg/d) [45] administration, or 6-month therapy with either simvastatin (10 mg/d), rosuvastatin (10 mg/d) [39], pitavastatin (2 mg/d), or pravastatin (10 mg/d) [39].…”
Section: Effects Of Statins On Fluorodeoxyglucose-positron Emission T...mentioning
confidence: 99%
“…Twenty-four prospective clinical trials have assessed the influence of statins on carotid plaque vulnerability concomitantly with the modulation of circulating inflammatory biomarkers. Based on imaging indices of plaque vulnerability, such as PET scans [47,[48][49][50]52] and carotid plaque echogenicity [53,54], most of those studies suggested an improvement in plaque stability after statin administration, accompanied by a significant reduction in inflammatory biomarkers. Those studies used the most known inflammatory biomarkers, like CRP [47][48][49][53][54][55][56][57][58][59], interleukin (IL)-6 [53,[55][56][57]59], tumor necrosis factor (TNF)-a [49,54,56,59], and monocyte chemoattractant protein-1 [49].…”
Section: Inflammatory Biomarkersmentioning
confidence: 99%
See 2 more Smart Citations
“…By lowering levels of low-density lipoprotein-bound cholesterol, AC can reduce the risk of atherosclerosis. The efficacy and safety of AC in facilitating the primary and secondary prevention of cardiovascular events have been demonstrated in various clinical trials [1][2][3]. However, due to the diverse genetic characteristics of metabolism and high drug plasma exposure, individual differences exist in clinical efficacy and adverse events, especially statin-induced myopathy [4,5].…”
Section: Introductionmentioning
confidence: 99%